Building Validity Evidence for Performance-Based Assessments: A Review and Reconceptualization of Response Processes Validity of Raters in Veterinary Medicine - Hall, Laureen P.; Hecker, Kent G. (Imagining SoTL, 2026)
Performance-based assessments (PBAs) are essential tools in veterinary medical education for evaluating students’ clinical and professional competencies. This reflection on assessment is grounded in the first author’s experience as a veterinary educator navigating the complexities of PBAs and in the second author’s experience as a psychometrician studying validity claims about raters’ cognitive processes as they use PBAs. By integrating personal insights with existing literature, this work contributes to the ongoing discourse on assessment design and defensibility in health professional education. Our aim is to highlight the need to explore how rater response processes influence assessment outcomes and to advocate for more robust, contextually relevant validity evidence in veterinary medical education.While multiple sources of validity evidence are needed to support decisions based on PBA scores, the response processes of raters—how they interpret and apply assessment criteria—remain underexplored in health profession education. Without this type of evidence, the defensibility of assessment scores, as well as the decisions based on them, may be compromised. We argue that understanding rater decision making is crucial for strengthening the validity argument of PBAs.